A Cluster Analysis of Pediatric Cancer Incidence Rates in Florida: 2000–2010 - Amin, Raid; Hendryx, Michael; Shull, Matthew; Bohnert, Alexander (Statistics and Public Policy, 2014)
This study uses disease surveillance cluster analysis methods to identify clusters for the three most common pediatric cancers in Florida (brain tumors, leukemia, lymphoma). In addition to a univariate purely spatial analysis, a space–time analysis is done, followed by a nonparametric permutation test for space–time interaction. This is followed by a multivariate spatial analysis for the three pediatric cancer types together. The main findings include a significant spatial cluster for each of the three cancer types covered in this study, in addition to identifying two significant clusters for all pediatric cancer types combined.